(untitled) (Ciudades, 2017)
The aim of the article is about the urban integral policies in neighbourhoods. At this sense, the author organizes the text in three sections: on the neighbourhood concept, the neighbourhoods’ urban policies in Catalonia; needs, challenges and elements for a better public intervention in neighbourhoods.